Consumption expenditure effects of adoption against drought tragedy in drought prone area of Eastern Hararghe, Ethiopia - Mume, Jafer; Haji, Jema; Jaleta, Moti; Jemal, Kedir (Springer Nature, 2025)
Annual consumption expenditure of the households seriously affected by climate shocks in the country where the major livelihood of the community depends on rain based agriculture where adaptation should be key strategy against climate shocks effect. This study investigated the effects of crop diversification and irrigation practices adoption on consumption expenditure against drought in drought prone area of Eastern Hararghe. Both primary and secondary data was used for this study. Irrigation practices and crop diversification practices were mainly practiced and considered as climate smart agricultural practices here. Multistage procedure applied and data collected from 430 samples during 2023 year. From Hararghe zone four districts were randomly selected. To investigate effects of crop diversification and irrigation practices on consumption expenditure two-stage least square model was used. Three months scales’ standard precipitation index was applied to analysis drought using 33 years rainfall data. Result revealed that livestock, drought experience, labor, adopting crop diversity, irrigation practices and household income positively increased consumption expenditure whereas market distance, family size and drought affected negatively. So, it is crucial to more advances farmers and experts’ information on climate shocks particularly drought and adoption practices that minimize drought effects. The policymakers ought to develop farmers’ income generating activities and weather related information service to enhance adoption of crop diversification and irrigation facilities to combat the current and future drought effect.